2011
DOI: 10.1371/journal.pone.0019095
|View full text |Cite
|
Sign up to set email alerts
|

4-Aminobutyrate Aminotransferase (ABAT): Genetic and Pharmacological Evidence for an Involvement in Gastro Esophageal Reflux Disease

Abstract: Gastro-esophageal reflux disease (GERD) is partly caused by genetic factors. The underlying susceptibility genes are currently unknown, with the exception of COL3A1. We used three independent GERD patient cohorts to identify GERD susceptibility genes. Thirty-six families, demonstrating dominant transmission of GERD were subjected to whole genome microsatellite genotyping and linkage analysis. Five linked regions were identified. Two families shared a linked region (LOD 3.9 and 2.0) on chromosome 16. We used tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…For example, potent inhibitors of GABA‐AT have been developed to treat epilepsy and addictions . In addition to the beneficial effects on neurodegenerative diseases, inhibition of GABA‐AT may be useful in immunomodulation and gastroesophageal reflux disease (GERD) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, potent inhibitors of GABA‐AT have been developed to treat epilepsy and addictions . In addition to the beneficial effects on neurodegenerative diseases, inhibition of GABA‐AT may be useful in immunomodulation and gastroesophageal reflux disease (GERD) …”
Section: Introductionmentioning
confidence: 99%
“…19 In addition to the beneficial effects on neurodegenerative diseases, inhibition of GABA-AT may be useful in immunomodulation 20 and gastroesophageal reflux disease (GERD). 21 Inhibition of OAT is proposed to be beneficial in treating hyperammonemias by enhancing the urea cycle to clear excess ammonia. 22,23 Recently, human OAT was shown to play a role in regulating mitotic cell division in rapidly growing cells and became a potential target for the development of chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, gene mutations leading to ABAT deficiency are extremely rare, while a clinical study biochemically confirmed that ABAT deficiency contributes to symptoms related to psychomotor retardation, hypotonia, hyperreflexia, lethargy, and intractable seizures (11). Moreover, ABAT single-nucleotide polymorphisms have been associated with depression (12), sleep homeostasis (13), autism (14) and gastroesophageal reflux disease (15). In regards to human cancer, reduced ABAT expression has been associated with resistance to endocrine therapy of breast cancer, and with poor recurrence-free survival of breast cancer patients (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…In Gastroesophageal reflux disease (GERD), Obesity patients have a high risk of acquiring the disease [23]. Results show that ABAT is a genetic risk factor for GERD, which strengthens the significance of this gene in Obesity [24]. "ACAS2L" is a known Obesity candidate gene [25] and Obesity is a proved cardiovascular disease risk factor [26].…”
Section: Resultsmentioning
confidence: 99%
“…And "pi" in reaction 2700 is a key component in the disturbance of Diabetes [31]. While in Obesity, 4-aminobutyrate transaminase (ABAT) has demonstrated the importance in Obesity [24]. Reaction 248 has the name Acyl CoA synthetase.…”
Section: Resultsmentioning
confidence: 99%